2011
DOI: 10.1128/aem.05661-11
|View full text |Cite
|
Sign up to set email alerts
|

Differential Bacteriophage Mortality on Exposure to Copper

Abstract: Many studies report that copper can be used to control microbial growth, including that of viruses. We determined the rates of copper-mediated inactivation for a wide range of bacteriophages. We used two methods to test the effect of copper on bacteriophage survival. One method involved placing small volumes of bacteriophage lysate on copper and stainless steel coupons. Following exposure, metal coupons were rinsed with lysogeny broth, and the resulting fluid was serially diluted and plated on agar with the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
23
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 34 publications
7
23
1
Order By: Relevance
“…3c suggest that actinic light induces highly oxygenated radicals on TiO 2 leading to E. coli damage. This damage allows Cu-ion(s) translocation/permeation across the cell membrane in agreement with work reported by Hashimoto/Fujishima et al [1][2][3][4], Li et al [5] and Ditta et al [6].…”
Section: Results An Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…3c suggest that actinic light induces highly oxygenated radicals on TiO 2 leading to E. coli damage. This damage allows Cu-ion(s) translocation/permeation across the cell membrane in agreement with work reported by Hashimoto/Fujishima et al [1][2][3][4], Li et al [5] and Ditta et al [6].…”
Section: Results An Discussionsupporting
confidence: 82%
“…Photocatalysis using TiO 2 combined with Cu have shown to have a stronger performance compared to TiO 2 when eliminating toxic pollutants and when inducing bacterial due to the electron acceptor properties of the Cu-ions. Antibacterial studies reporting some the activity by TiO 2 /Cu photocatalysts have recently been reported by Hashimoto/Fujishima [1][2][3][4], suggesting that UV-light induces highly oxygenated radicals on TiO 2 damaging the outer cell wall followed by Cu-ion(s) infiltration across the cell membrane in agreement with observations reported by Li and Dennehy [5] and Ditta et al [6]. More recently the TiO 2 /Cu has been revisited to improve bacterial reduction under light and in the dark addressing the synthesis of uniform, robust adhesive films sputtered on textiles and polymers by our laboratory [7][8][9][10].…”
Section: Introductionsupporting
confidence: 60%
“…In dry touch contamination viral inactivation is extremely rapid, with the highest rate of inactivation occurring in the first 5 minutes. The process appears to be a result of a combination of copper action and drying process followed by a slower rate of inactivation; Li and Dennehy [41] observed that bacteriophages also lost infectivity on copper but as soon as the inoculum dried no further inactivation occurred and Abad et al [42] observed that the drying process affected persistence of poliovirus and adenovirus on environmental fomites. Sharps et al [43] observed that virus retained infectivity in transfer ‘wet’ fomite from stainless steel to fingertips and fruits but transfer was reduced if contaminating inoculum was allowed to dry.…”
Section: Discussionmentioning
confidence: 99%
“…This bacterial inactivation by Cu-species in the dark and/or under anaerobic conditions has been attributed to the translocation/permeation of Cu-ions across the bacterial cell wall. Bacterial reduction mediated by Cu-NPs has been recently reported in suspensions or on sputtered surfaces [37][38][39][40][41][42]. We suggest that the bacterial inactivation in the dark on Cu sputtered PES proceeds in air by CuO/Cu(OH) 2 (NPs) and the production of O 2 − radicals [34,35].…”
Section: Introductionmentioning
confidence: 99%